Honey Bees in the Tropics Show Winter Bee-Like Longevity in Response to Seasonal Dearth and Brood Reduction - Feliciano-Cardona, Stephanie; Döke, Mehmet Ali; Aleman, Janpierre; Agosto-Rivera, Jose Luis; Grozinger, Christina M.; Giray, Tugrul (Frontiers in Ecology and Evolution, 2020)
Upon their first introduction to Americas in 1956, African honey bees (Apis mellifera scutellata) hybridized with the previously introduced and already established European honey bees (EHBs). The resulting Africanized honey bees (AHBs) have spread through the continental tropics of the Western Hemisphere. The expansion of AHB has been constrained in temperate climates generally thought to be because of a lack of key adaptations required for successful overwintering. A drastic increase in longevity during broodless periods is crucial to colony survival. In the temperate context, broodlessness happens in winter. While tropical regions do not experience winters as temperate zones do, seasonal changes in the abundance of floral resources cause variation in brood levels throughout the year. Here we use an island population of AHB in Puerto Rico (gAHB) to test the capacity of tropical-adapted honey bees to alter their longevity in different seasons, as well as under brood manipulation. We found that worker longevity in the gAHB colonies increases in the wet season (maximum longevity ca. 88 days vs 56 days) in response to dearth of floral resources. A more pronounced increase in longevity was observed in response to manipulative reduction of the amount of open brood (maximum longevity 154 days). In addition, long lived gAHB demonstrated the signature winter bee-like hypopharyngeal gland size (average acini diameter 100.8 ± 6.2 µm at 65 and 70 days of age, N=26), intermediate between forager (88.7 ± 5.9 µm, N=24) and nurse (129.5 ± 8.1 µm, N=24) gland size. We showed that gAHBs do not lack the adaptation to alter their longevity seasonally, though the magnitude of changes is less intense than those observed in EHBs during temperate winters. This suggests that increased longevity in response to limited capacity to rear brood is a shared character of Africanized and European honey bees.